Absence of OsβCA1 causes a CO2 deficit and affects leaf photosynthesis and the stomatal response to CO2 in rice. (20th March 2017) - Chen, Taiyu; Wu, Huan; Wu, Jiemin; Fan, Xiaolei; Li, Xianghua; Lin, Yongjun
Summary: Plants always adjust the opening of stomatal pores to adapt to the environment, for example CO2 concentration ([CO2 ]), humidity and temperature. Low [CO2 ] will trigger the opening of stomatal pores to absorb extra CO2 . However, little is known about how CO2 supply affects the carbon fixation and opening of stomatal pores in rice. Here, a chloroplast‐located gene coding for β‐carbonic anhydrase (βCA) was found to be involved in carbon assimilation and the CO2 ‐mediated stomatal pore response in rice. Os β CA1 was constitutively expressed in all tissues and its transcripts were induced by high [CO2 ] in leaves. Both T‐DNA mutant and RNA interference lines showed phenotypes of lower biomass and CA activities. Knockout of Os β CA1 obviously decreased photosynthetic capacity, as demonstrated by the increased CO2 compensation point and decreased light saturation point in the mutant, while knockout increased the opening ratio of stomatal pores and the rate of water loss. Moreover, the mutant showed a delayed response to low [CO2 ], and stomatal pores could not be closed to the same degree as those of wild type even though the stomatal pores could rapidly respond to high [CO2 ]. Genome‐wide gene expression analysis via RNA sequencing demonstrated that the transcript abundance of genes related to Rubisco, photosystem compounds and the opening of stomatal pores was globally upregulated in the mutant. Taken together, the inadequate CO2 supply caused by the absence of Os β CA1 reduces photosynthetic efficiency, triggers the opening of stomatal pores and finally decreases their sensitivity to CO2 fluctuation. Significance Statement: Contrary to Arabidopsis βCA1 with a dominant role in cotyledons, we showed that OsβCA1 plays a key role in CO2 ‐mediated stomatal opening and supplying adequate carbon for the chloroplasts in mature rice leaves. Deficiency of OsβCA1 decreased the sensitivity of stomatal pores to CO2 fluctuation, reduced biomass accumulation, modified photosynthesis gene expression, increased the CO2 compensation point and lowered the light saturation of photosynthesis in rice.